Guest

(1+cotA+tanA)(sina-cosa)/sec ^3a-cosec ^ 3a=sin ^ 2A.cos ^ 2A prove that

(1+cotA+tanA)(sina-cosa)/sec ^3a-cosec ^ 3a=sin ^ 2A.cos ^ 2A prove that

Grade:10

2 Answers

Harsh Patodia IIT Roorkee
askIITians Faculty 907 Points
5 years ago
PFA228-426_5.PNG
Aaranys
11 Points
4 years ago
LhsDenominator:(secA-cosecA)(sec^2+cosec^2A+secAcosecA)={(1+cosA/sinA+sinA/cosA) (sinA-cosA)}/(1/cosA -1/sinA)(1/cos^2A+1/sin^2A+1/sinAcosA){(SinAcosA +1/sinAcosA ) (sinA-cosA)}/(sinA-cosA/sinAcosA)(1+SinAcosA/cos^2Asin^A)(1+SinAcosA)(sinA-cosA)(sinAcosA)(sin^2A cos^2A)/(sinAcosA)(sinA-cosA)(1+sinAcosA)=sin^2Acos^A=RhsLhs=RhsHence Proved

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free